Moodle 2 administration : an administrator's guide to configuring, securing, customizing, and extending Moodle - Büchner, Alex (Community experience distilled., 2011)
Written in a clear, straightforward way with lots of screenshots and direct instructions, this book will equip you with all the tools you need to set up, optimize, extend, and maintain a Moodle system. A problem-solution approach has been taken when possible to bring the content more in line with your day-to-day operations. This book is written for technicians and systems administrators, as well as academic staff. Essentially anyone who has to administer a Moodle system. Whether you are dealing with a small-scale local Moodle system or a large-scale multi-site Virtual Learning Environment, thi.